2003
DOI: 10.1097/00002508-200301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Chronic Pain After Inguinal Herniorrhaphy

Abstract: The frequency of chronic pain after inguinal hernia repair was found to be as high as 54%, much more than previously reported. Quality of life of these patients is affected. Chronic pain is reported less often after laparoscopic and mesh repairs. Recurrent hernia repair, preoperative pain, day case surgery, delayed onset of symptoms, and high pain scores in the first week after surgery, however, were identified to be risk factors for the development of chronic pain. Definition of chronic pain was not explicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
326
3
26

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(364 citation statements)
references
References 46 publications
9
326
3
26
Order By: Relevance
“…Chronic groin pain has been reported in many studies (Erhan et al 28 reported 4-6% of patients having chronic pain after Lichtenstein and preperitoneal hernia repair and Phoolbalan et al 29 reported a 10% incidence of pain after inguinal herniorrhaphy). Several risk factors seems to play an important role in the development of chronic groin pain, such as surgeons experience, day care surgeries, intensity of immediate postoperative pain and degree of specialization 28,29 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic groin pain has been reported in many studies (Erhan et al 28 reported 4-6% of patients having chronic pain after Lichtenstein and preperitoneal hernia repair and Phoolbalan et al 29 reported a 10% incidence of pain after inguinal herniorrhaphy). Several risk factors seems to play an important role in the development of chronic groin pain, such as surgeons experience, day care surgeries, intensity of immediate postoperative pain and degree of specialization 28,29 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Several risk factors seems to play an important role in the development of chronic groin pain, such as surgeons experience, day care surgeries, intensity of immediate postoperative pain and degree of specialization 28,29 . One author quoted a 20% rate of nerve entrapment 30 but studies rarely mentioned whether surgeons identified the Ilioinguinal nerve or Iliohypogastric nerve during open dissection or not 31 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…This is consistent with other studies indicating that women experience greater pain than men after surgery. 12,13 DOI:10.1002/MSJ Women continued to report greater discomfort than men after discharge (P < 0.016) but did not differ from men in their level of physical activity. The authors concluded that initiation of thoracic epidural analgesia prior to incision did not significantly impact pain or physical activity.…”
Section: Anesthetic Factorsmentioning
confidence: 90%
“…17 Ochroch et al randomized 157 patients undergoing elective major open thoracotomy (either classic posterolateral or a muscle-sparing incision) to receive thoracic epidural analgesia initiated prior to incision or at the time of rib approximation. Pain and activity scores were obtained at 4,8,12,24,36, and 48 weeks after surgery. Overall, there were no differences in pain scores between the control and treatment groups during hospitalization (P > 0.165) or after discharge (P > 0.098).…”
Section: Anesthetic Factorsmentioning
confidence: 99%
“…Poobalanas ir kt. [20] apibūdi-no tris lėtinio skausmo sindromus po kirkšnies plastikos: somatinį, neuropatinį ir visceralinį. Cunninghamas ir kt.…”
Section: Diskusijaunclassified